O PIBID NO CODAP/UFS E A ABORDAGEM DA LITERATURA NA EDUCAÇÃO BÁSICA: PIBID IN CODAP/UFS AND THE APPROACH OF THE LITERATURE IN BASIC EDUCATION - NOVAIS, Urandi Rosa (Travessias Interativas, 2020)
RESUMO: O presente trabalho traz a campo algumas reflexões acerca das oficinas e atividades desenvolvidas pelos graduandos do Programa Institucional de Bolsas de Iniciação à Docência – PIBID, no Colégio de Aplicação da Universidade Federal de Sergipe – CODAP/UFS, nas aulas de Língua Portuguesa, especificamente na abordagem da Literatura, cujo objetivo foi investigar como as ações do PIBID contribuíram na abordagem da literatura na educação básica e sua colaboração no processo de ensino e aprendizagem dos discentes do CODAP/UFS. Os dados foram obtidos a partir da aplicação de um questionário para os alunos da 2ª série do Ensino Médio, turmas A e B, numa abordagem quali- quantitativa, cujos resultados foram interpretados a partir de estudos teóricos como, por exemplo, Cândido (2000), Jouve (2012), Soares (2011) Colomer (2007), entre outros, mostram-nos o quanto a participação dos graduandos do PIBID colabora no fortalecimento do ensino da literatura, e também no processo de formação deles enquanto futuros profissionais da educação básica. PALAVRAS-CHAVE: Educação Básica. Fomação Docente. Literatura. PIBID. ABSTRACT: The present work brings to the field some reflections about the workshops and activities developed by the graduates of the Institutional Program for Teaching Initiation Scholarships - PIBID, at the College of Application of the Federal University of Sergipe - CODAP/UFS, in Portuguese language classes, specifically in approach to Literature, whose objective was to investigate how PIBID’s actions contributed to the approach of literature in basic education and its collaboration in the teaching and learning process of Codap/UFS students. The data were obtained from the application of a questionnaire for the students of the 2nd grade of High School, classes A and B, in a quali-quantitative approach, whose results interpreted from theoretical studies such as, for example, Cândido (2000), Jouve (2012), Soares (2011) Colomer (2007), among others, show us how much the participation of PIBID undergraduates contributes to strengthening the teaching of literature and in their training process as future basic education professionals. KEYWORDS: Basic Education. Teacher Training. Literature. PIBID.